TP015/#1566 A phase 2, two-stage, study of mirvetuximab soravtansine (IMGN853) in combination with pembrolizumab in patients with microsatellite stable (MSS) recurrent or persistent endometrial cancer (EC). (4th December 2022) - Porter, Rebecca; Tayob, Nabihah; Polak, Madeline; Sawyer, Hannah; Gardner, Jeanette; Campos, Susana; Krasner, Carolyn; Lee, Elizabeth; Liu, Joyce; Stover, Elizabeth; Veneris, Jennifer; Wright, Alexi; et al.
Abstract : Objectives: Folate receptor-alpha (FRα) expression is associated with poor prognosis in endometrial cancer (EC). Mirvetuximab soravtansine (MIRV), an antibody drug conjugate (ADC) comprising a FRα-binding antibody, cleavable linker, and the tubulin-disrupting maytansinoid DM4, showed tolerability and single agent activity in a Phase 1 dose expansion study in FRα+ advanced/recurrent EC (NCT01609556 ). In addition to direct target-mediated cytotoxicity, MIRV activates monocytes and promotes phagocytosis of tumor cells through Fc-FcγR interactions. We hypothesized that addition of MIRV may improve the low response to immunotherapy in MSS EC. Methods: This is a Phase 2, single cohort study of MIRV with pembrolizumab in recurrent/persistent EC (NCT03835819 ). Patients must have advanced or recurrent MSS serous EC with FRα expression (≥50% of cells with ≥2+ by IHC performed at Ventana, Inc) and have received 1–3 prior lines of therapy. Prior receipt of ICI is allowed. Patients receive MIRV 6 mg/kg AIBW and pembrolizumab 200 mg every 21 days. The co-primary endpoint is progression-free survival at 6 months and objective response rate by RECIST 1.1. Translational objectives include assessment of tumor-infiltrating immune cells, expression of immune checkpoint markers, and whole exome sequencing. Statistical considerations are for a Simon two-stage optimal design with 16 patients in Stage 1 and 19 patients in Stage 2, to a total of 35. Prespecified activity for the first stage of accrual was met; second stage accrual began November 2020. Results: Trial in progress: no available results at time of submission. Conclusions: Trial in progress: no available results at time of submission.